2020
DOI: 10.1186/s13023-020-01517-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, mortality and healthcare economic burden of tuberous sclerosis in Hong Kong: a population-based retrospective cohort study (1995–2018)

Abstract: Background We aim to elucidate the disease impact by accounting the prevalence, survival rate, genetics, mTOR inhibitor use and direct costs of tuberous sclerosis complex (TSC) in our local setting. TSC patients with documented visits to our local public hospitals in 1995–2018 were identified. The public hospitals captured most if not all local TSC patients. Demographics such as age, sex, death, genetic profiles were retrieved from the central electronic database. Data including prevalence, age distribution an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
(56 reference statements)
3
7
1
Order By: Relevance
“…The cost of mTOR inhibitor use is likely to decrease in the future as generic formulations become available, a phenomenon that has been well-demonstrated for other ASDs [ 25 , 46 ]. Although our study appears to agree with other COI studies regarding the contributions of hospitalization and ASD use [ 11 , 13 , 32 , 33 , 35 , 36 , 39 , 40 , 47 , 48 ] (for details, please refer to Table 7 ) performing direct comparisons against studies from different settings and different countries proved to be difficult, as the observed variations were likely associated with a variety of contributing factors including differences in definition, policy, measurements, and population (such as the combination of TSC/epilepsy cohorts). Furthermore, the resource use might change over time according to changes in organ manifestation during the lifetime of TSC patients [ 3 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…The cost of mTOR inhibitor use is likely to decrease in the future as generic formulations become available, a phenomenon that has been well-demonstrated for other ASDs [ 25 , 46 ]. Although our study appears to agree with other COI studies regarding the contributions of hospitalization and ASD use [ 11 , 13 , 32 , 33 , 35 , 36 , 39 , 40 , 47 , 48 ] (for details, please refer to Table 7 ) performing direct comparisons against studies from different settings and different countries proved to be difficult, as the observed variations were likely associated with a variety of contributing factors including differences in definition, policy, measurements, and population (such as the combination of TSC/epilepsy cohorts). Furthermore, the resource use might change over time according to changes in organ manifestation during the lifetime of TSC patients [ 3 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…In terms of the use of healthcare resources, our results appear to be in line with other COI studies, particularly hospitalization frequency and the use of ASDs [ 9 , 11 , 15 , 16 , 37 , 42 , 44 , 45 ]. Most studies could not evaluate mTOR inhibitor use because the periods of data inclusion preceded their authorization.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies could not evaluate mTOR inhibitor use because the periods of data inclusion preceded their authorization. In our study, more patients (37%) used mTOR inhibitors than in three other recent studies (8–16.5%) [ 37 , 44 , 45 ].…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Tuberous sclerosis complex (TSC) is a rare genetic disorder with a prevalence of up to 1 in 5000 individuals that is caused by genetic variations in either the TSC1 or TSC2 gene, which result in the loss of function [1][2][3]. Both genes encode components of the hamartin-tuberin complex and serve as tumour suppressor genes by downregulating cell proliferation and differentiation via mechanistic target of rapamycin (mTOR) [4,5].…”
Section: Introductionmentioning
confidence: 99%